Influence of the Municipal Digital Communication of Guayaquil: Citizen Participation and Transparency - Chica Pincay, José (Revista Universidad de Guayaquil, 2024)
The research focuses on the influence of municipal digital communication in Guayaquil on citizen participation and transparency. With the growing importance of digital interaction, we seek to understand how digital communication impacts citizens and government transparency. The objective is to analyze the relationship between municipal digital communication, citizen participation and transparency. The research was carried out at the University of Guayaquil, the municipal library, and neighborhoods of the Tarqui parish, with a focus on public, private and independent workers, covering a probabilistic sample of 385 people and the Municipal IT director. The research adopted a mixed approach with quantitative and qualitative methods, using semi-structured interviews and structured questionnaires. Data collection was carried out in person, organized, and systematized with Excel. The Likert scale was used to measure the variables. The results indicated a significant relationship between municipal digital communication, citizen participation and transparency. Data analysis was carried out with Cronbach's alpha, validating the confidence in the results. This research contributes to the understanding of how municipal digital communication can improve citizen participation and transparency. The findings of greater attention to municipal services as well as the diversification of digital content are relevant for the development of effective communication strategies at the municipal level, thus contributing to the strengthening of local democracy.
Keywords: Public administration; Electronic government; Digital platform; Public information; Public participation